2007
DOI: 10.1007/s00394-006-0630-y
|View full text |Cite
|
Sign up to set email alerts
|

Long-term consumption of fermented soybean-derived Chungkookjang enhances insulinotropic action unlike soybeans in 90% pancreatectomized diabetic rats

Abstract: Based on these results, the fermentation of soybeans predominantly with Bacillus subtilis generated isoflavonoid aglycones and small peptides, which improved insulinotropic action in islets of type 2 diabetic rats. Overall, the anti-diabetic action of CKJ was superior to CSB in type 2 diabetic rats.

Help me understand this report

Search citation statements

Order By: Relevance

Paper Sections

Select...
3
1
1

Citation Types

0
72
0
1

Year Published

2011
2011
2019
2019

Publication Types

Select...
6
2

Relationship

2
6

Authors

Journals

citations
Cited by 76 publications
(73 citation statements)
references
References 31 publications
0
72
0
1
Order By: Relevance
“…In addition, Chungkookjang potentiated insulin/IGF-1 signaling in islets via the induction of insulin receptor substrate-2 expression, leading to increased pancreatic duodenal homeobox-1, insulin promoter transcription factor. In parallel with the enhancement of the signaling, Chungkookjang elevated pancreatic beta-cell hyperplasia by increasing its proliferation and decreasing apoptosis [34] .…”
Section: Fermented Unsalted Soybeansmentioning
confidence: 99%
“…In addition, Chungkookjang potentiated insulin/IGF-1 signaling in islets via the induction of insulin receptor substrate-2 expression, leading to increased pancreatic duodenal homeobox-1, insulin promoter transcription factor. In parallel with the enhancement of the signaling, Chungkookjang elevated pancreatic beta-cell hyperplasia by increasing its proliferation and decreasing apoptosis [34] .…”
Section: Fermented Unsalted Soybeansmentioning
confidence: 99%
“…Soy proteins are rich in arginine and glycine, which are involved in insulin and glucagon secretion from the pancreas. Decreased plasma insulin by soy yoghurt may be due to decreased release from the pancreas or increased hepatic removal [55]. Thus, the decrease in cholesterol seen with soy protein in soy yoghurt may be due to the decreased insulin-glucagon ratio caused by arginine and glycine.…”
Section: Antidiabeticmentioning
confidence: 99%
“…The expression of hepatic ACS (acyl-CoA synthase), CTP-1 (carnitine palmitoyltransferase-1), ACO (acyl-CoA oxidase), and UCP2(uncoupling protein-2) were increased by chungkukjang supplementation. The data demonstrated that chungkukjang supplementation leads to increased mRNA expressions of enzymes and protein involved in fatty acid oxidation in liver, reduced accumulation of body fat and improvement of serum lipids in high fat diet fed mice (Kwon et al, 2007a;Soh et al, 2008). In addition, the hepatic transcriptional profiles using cDNA microarray showed that several genes involved in fatty acid catabolism (Acaa2, Mgll, Phyh, Slc27a2, Slc27a5), which were the main genes that had altered expressions by high fat diet, were normalized by chungkukjang consumption (Table 5) (Soh et al, 2011).…”
Section: Chungkukjangmentioning
confidence: 94%
“…Yang et al, 2003). In addition, dietary supplementation with chungkukjang exerted not only hypoglycemic effects but also antioxidant effects in diabetic rats (Kwon et al, 2007a). After fermentation, isoflavonoid glycones are changed into isoflavonoid aglycones, which seem to have greater anti-diabetic activity than do isoflavonoid glycones (Table 1, 2, 3) .…”
Section: Chungkukjangmentioning
confidence: 99%
See 1 more Smart Citation